Validation of the Greek version of Mini Tinnitus Questionnaire as a Brief Screening Test for Assessment of Tinnitus‐related Distress: our experience in 301 adult patients. (August 2015) - Panagiotopoulos, G.; Galanakis, M.; Varvogli, L.; Chrousos, G.; Darviri, C.
<x xml:space="preserve">Abstract</x> Objectives Validation of the Greek version of Mini Tinnitus Questionnaire (Mini‐TQ‐GR) as a Brief Screening Test for Assessment of Tinnitus‐related Distress. Design Questionnaire study. Setting 401 General Military Hospital of Athens/Department of Audiology – Neurootology, Athens, Greece. Participants Three hundred and one participants have anonymously completed the Mini‐TQ‐GR, comparing it to the Perceived Stress Scale (PSS 14) and Multidimensional Health Locus of Control Scale (MΗLoC) from November 2013 until May 2014. Main outcome measure Mini‐TQ‐GR, compared to PSS 14 and MΗLoC. Results Factor analysis, has shown that the Mini‐TQ‐GR includes three main factors (Distress, Health pre‐occupation and Depression), which explains the 59.05% of the total variance. The Cronbach alpha index was 0.865 approaching the respective reliability factor of the original validation (0.9). The test–retest correlation (intraclass correlation coefficient) was 0.9 (P < 0.01), close to the results of the original study (0.89). We found a positive correlation between tinnitus and perceived stress (r = 0.349**) and negative correlation between tinnitus and external locus of control (r = −0.124*, r = −0.198**) (chance, others). Conclusions This study demonstrated that the Mini‐TQ‐GR has good internal consistency and reliability becoming a useful, validated measurement tool for tinnitus‐induced distress.